EVALUATION OF THE MINIMUM SERVICE STANDARDS POLICY FOR HYPERTENSION HEALTH SERVICES AT BIROBULI COMMUNITY HEALTH CENTER, PALU CITY - Suasa, Suasa; Rapi, Muhammad (CV. Lafadz Jaya, 2024)
This study aims to evaluate the achievement of the Minimum Service Standards (SPM) for Hypertension health services at the Birobuli Community Health Center. This research adopts a descriptive type with a qualitative approach. Data collection techniques involved observation, interviews, and documentation. Data analysis used the interactive model of Miles and Huberman, consisting of data condensation, data presentation, and conclusion drawing. The results showed that overall, the implementation of the Minimum Service Standards (SPM) policy at Birobuli Community Health Center was quite effective, efficient, and met the standards of adequacy, equity, responsiveness, and appropriateness. Despite some obstacles, the Birobuli Health Center has made efforts to overcome them.